Transition Metal Complexes of Oxygen and Nitrogen Containing Schiff Base Derived from 4-Methyl-1,2-dihydro-2-oxoquinazoline - Rai, B.K.; Anand, Rahul (Asian Journal of Chemistry, 2012)
Co(II), Ni(II) and Cu(II) complexes of 4-methyl-1,2-dihydro-2-oxoquinazoline were synthesized and characterized by molar mass, elemental analyses, infrared spectra, electronic spectra, conductivity and magnetic measurements. The analytical data proposes the composition of the metal complexes to be ML2X2; where M = Co(II), Ni(II); X = Cl–, Br–, I– and NO3– and M = Cu(II), X = X = Cl–, Br– and NO3–; L = 4-methyl-1,2-dihydro-2-oxoquinazoline hydrazone. IR results demonstrate the bidentate binding of the Schiff base involving azomethine nitrogen and carbonyl oxygen. The electronic spectral measurements proposes Co(II), Ni(II) have octahedral geometry, where Cu(II) complexes have distorted octahedral geometry.